Unintentional synchronization with self-avatar for upper- and lower-body movements - Boban, Loën; Strauss, Lucas; Decroix, Hugo; Herbelin, Bruno; Boulic, Ronan (Frontiers in Virtual Reality, 2023)
The subjective experience of embodying an avatar when immersed in virtual reality (VR) is known to support the sense of presence and to help with the interaction in a virtual environment. Virtual embodiment is often thought of as the consequence of a replacement of the physical body by a virtual one, with a sense of agency for the avatar obtained by making the avatar’s body follow the user’s movements. This unidirectional motor link was however challenged by studies observing the opposite effect under different circumstances, for example in a slow-motion context or when an arm movement was snapped on a predefined axis. These reports are however still rare or anecdotal. With the idea of a generalized bidirectional relationship between user and avatar in mind, we established a methodology to systematically provoke and study the circumstances under which participants follow the movements of their avatar during long repetitive movements without having been instructed to do so. A preliminary study confirmed that our virtual experimental setup, using full-body motion capture, avatar animation and virtual mirrors, supports a strong sense of agency and body ownership for the avatar while enabling the experimental manipulation of the avatar’s movement. In the main experimental study, where participants performed repetitive upper- and lower- body movements while their avatar animation was either congruent or out-of-phase, we observed that almost all participants synchronized with their avatar at least once, for ~47% of trials for lower limb movements and ~38% for upper limb movements. Participants still reported low agency and ownership for the avatar under the incongruent condition but, most interestingly, some of them also reported that their movements were not influenced by the avatar despite the behavioural effect. Our methodological approach and results contribute to a characterization of the conditions of occurrence of the self-avatar follower effect, and thereby to identify enriched interaction design for VR involving complex avatar-user mutual interdependencies.